Conceptualization of Crises and Organizational Healing in India: Integrating Culture and Practice - Dwarakanath, Nivedita (Journal of management, spirituality & religion, 2026)
Organizational healing is an important construct examining how organizations repair and strengthen their collective social fabric and functioning after experiencing trauma, crisis, or significant disruption. However, while this field is gaining attention, current research is largely rooted in Western contexts and based on studies of specific crises, which may not have universal applicability. This paper proposes that a profound and culturally rich understanding of organizational healing can be achieved by incorporating perspectives from Indian knowledge systems. In Indian indigenous traditions, healing is viewed holistically, going beyond merely curing a condition to encompass a process that restores harmony, balance, and peace, fostering an inner sense of well-being and connection between mind, body, and spirit. Presenting excerpts from various ancient Indian texts and drawing primarily from the Santi Parva of Mahabharata, we explain how these systems often emphasize relational processes and collective support as crucial for healing. By integrating this Indianness into the study of organizational healing, we can illuminate unique insights into how organizations might navigate adversity. This theoretical exploration suggests that culturally grounded approaches can enhance collective well-being and robustness, offering a valuable alternative or complement to existing frameworks and paving the way for culturally sensitive organizational practices and future research.